Gaya Kepemimpinan Kepala Sekolah Dasar Negeri Kawatuna Kecamatan Mantikulore Kota Palu - Pratama, Bayu Agung; Sussanti, Sussanti (Jurnal ADMINISTRATOR, 2024)
This research aims to determine the leadership style of the Principal of the Kawatuna State Elementary School, Mantikulore District, Palu City. The research basis used in this research is qualitative with a descriptive approach. Data collection techniques in this research are observation, interviews and documentation. The informants in this research were class teachers and BP (Guidance Counseling) teachers. Meanwhile, the data analysis used in this research is data collection, data reduction, data presentation and drawing conclusions. The theory used in this research is the theory put forward by Hersey and Blanchard, which classifies situational leadership style into four indicators, namely: instruction, consultation, participation and delegation. The research results show that the four indicators of situational leadership can be seen from the leadership style displayed by the principal of the Kawauna state elementary school. In the instruction indicator, the principal can direct all teachers working in the school, this proves that the principal has carried out his function as a leader. In the consultation section, it was seen that the principal carried out two-way interactions, there was a process of providing ideas and suggestions and it was also seen that the principal accepted the ideas, suggestions and input given by the teachers. Meanwhile, in the participation section, it can be seen that there was involvement of all parties, including deputy principals and teachers at the Kawauna State Elementary School. However, in the delegation section, it can be seen that the delegation process given by the principal is limited and only occurs under certain conditions. The limitations on granting delegation are based on the main tasks and functions of each party